Mediasi Massal Terorisme: Pengantar Critical Terrorism Studies - Aly Ashghor, Aly Ashghor (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2018)
This paper is a development of research conducted by the Center for National Security Studies (Puskamnas) Bhayangkara University of Jakarta on a map of global terrorism obtained from coverage of 56 (fifty-six) online mass media in the world throughout the year 2017. Mass mediation of terrorism is a critical effort and a reflective way in trying to understand the practice and the articulation of the terrorism discourse in the world, especially on how the media enters and enlivens the practice of terrorism concept. This paper shows that the social construction of terrorism tends to be influenced by the Western mass media. In the construction of the mass media, the notion of terrorism today is the product of the discourse of the Western mass media. The dominance of the Western mass mediation terrorism resulted in the construction of terrorism discourse associated with the movement of Islamism and Communism. The mass mediation of terrorism demonstrated by Israeli atrocities against Palestinians tends to disregard acts of state terrorism. Therefore, the implication of state-centered terrorism in counter-terrorism policies is more oriented towards national security than human security.